(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores national wrestling as a comprehensive activity aimed at preserving, protecting, and advancing the culture and values of one’s nation. It emphasizes the importance of promoting national wrestling among women, particularly in the contemporary world, where women play a vital role as key builders of society. The discussion includes strategies for shaping and developing national wrestling while addressing the opportunities and challenges faced by women in this endeavor.